PERANAN AKUNTANSI PERTANGGUNGJAWABAN BIAYA PADA BADAN PERENCANAAN, PEMBANGUNAN, RISET DAN DAERAH - Waroh, Vety Muna; Bullah, Habi (ITB AAS Indonesia Surakarta, 2024)
The Planning, Development, Research and Regional Agency (Bapperida) was formed based on the needs, development and progress of the government sector and specifically assists regional governments in implementing development in the government sector. Responsibility accounting is an accounting system that assigns responsibility to a responsibility center which will ultimately be measured to determine the performance of the center concerned. The research used in this article is descriptive with a qualitative approach. Based on the results obtained from Bapperida Pamekasan's calculations and the results of the author's interview, it can be explained that in 2021 the percentage was 87.01%, in 2022 the level of effectiveness experienced a quite drastic increase, namely 8.09% to 95.10%. In 2023 the level of effectiveness will decrease by 2.1% to 97.20%, this exceeds the percentage value of the level of effectiveness in 2021. So the trend in the role of cost responsibility accounting in the Planning, Development, Research and Regional Agency of Pamekasan Regency can be said to be in the criteria effective so the results of this study are considered positive. Keywords: Responsibility accounting, Bappeda